Building Resilient Communities Through Sustainable Rural Tourism: The Contribution Of Village Sdgs To Human Resource Development - Pratiwi, Vina Andita; Utomo, Sudibyo Budi; Kamaludin, Ahmad (Migration Letters, 2024)
Purpose: The objective of this study is to investigate the relationships between Sustainable Development Goals (Village SDGs), Community Engagement, Technology Adoption, Local Governance Support, and Human Resource Development in rural communities. Methodology/approach: The study was conducted in various rural communities, employing a survey-based approach. Data were collected using a structured questionnaire administered through an online platform. The analysis was performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, implemented through the SMART PLS software. Results/findings: The findings of this study reveal that Sustainable Development Goals (Village SDGs) have a positive effect on Local Governance Support, Community Engagement positively influences Local Governance Support, Technology Adoption has a positive impact on Local Governance Support, and Local Governance Support promotes Human Resource Development. Moreover, Local Governance Support was found to partially mediate the relationship between Sustainable Development Goals (Village SDGs) and Human Resource Development. Limitations: One limitation of this study is that it focused on a specific context, and the findings may not be generalizable to all rural communities. Additionally, the study relied on self-reported data, which may introduce response bias and measurement errors. Contribution: This study contributes to the understanding of the interrelationships between Sustainable Development Goals (Village SDGs), Community Engagement, Technology Adoption, Local Governance Support, and Human Resource Development in rural areas. The findings provide insights for policymakers, local governance bodies, and community development practitioners to formulate strategies that prioritize Sustainable Development Goals (Village SDGs), foster community engagement, promote technology adoption, and strengthen local governance support. This study contributes to the fields of rural development, sustainable development, and human resource management. Novelty: The novelty of this study lies in its examination of the mediating role of Local Governance Support in the relationships between Sustainable Development Goals (Village SDGs) and Human Resource Development, as well as between Technology Adoption and Human Resource Development. This study adds to the existing literature by highlighting the importance of effective governa[1]nce practices and community engagement in promoting sustainable development outcomes and enhancing human resource capacities in rural communities.